Renal Function Evaluation in Secondary Amyloidosis According to Location of Deposition - Serhat Özçelik; Gülizar Manga Şahin (Medical Laboratory Technology Journal, 2020)
It aimed to evaluate the renal functions according to the accumulation site of amyloid in patients diagnosed with secondary amyloidosis by renal biopsy. Fifty patients diagnosed with secondary amyloidosis, who referred to the nephrotic syndrome outpatient clinic included in the study. According to the findings of renal biopsy, only-glomerular amyloid deposition (group- 1) detected in 9 patients and glomerular+ tubulointerstitial deposition (group- 2) identified in 41 patients. Serum creatinine, creatinine clearance, and total proteinuria levels compared between groups at the time of presentation and on 3rd, 6th, 12th, and 24th months. Initial and subsequent serum creatinine, creatinine clearance, and total proteinuria levels not found to be significantly different between groups (p>0,05 for all). Among subjects with only-glomerular deposition, statistically significant descents in total proteinuria, when compared to initial levels, were observed from the beginning of the 6th month to the end of the 24th month (p